Changes to fine structure, size and mechanical modulus of phytoglycogen nanoparticles subjected to high-shear extrusion. (15th December 2022) - Roman, Laura; Baylis, Benjamin; Klinger, Karl; de Jong, Jondavid; Dutcher, John R.; Martinez, Mario M.
Abstract: This study aims to enhance the understanding of the structure of maize phytoglycogen nanoparticles, and the effect of shear scission on their architecture, radius, stiffness, and deformability. Compared to amylopectin, phytoglycogen had a lower A:B chain ratio, a lower number of chains per B chain, and a much higher number of Afingerprint chains. Phytoglycogen ( M w = 28.0 × 10 6 g/mol) was subjected to high-shear extrusion with varying Specific Mechanical Energies (SMEs) using different screw speeds, showing a maximum stable molecular weight M w of ∼9.31 × 10 6 g/mol and a particle radius R reduction of 36 %, with a corresponding 20 % increase in the average mass density. Atomic force microscopy force spectroscopy revealed that nanoparticles extruded at the lowest SME (122 Wh/kg) exhibited a 20 % increase in Young's modulus. Higher SME values (up to 488 Wh/kg) resulted in an overall decrease in stiffness without further significant reductions in radius. Graphical abstract: Unlabelled Image